Meretas Jalan Peningkatan Pengetahuan Wisatawan Terhadap Bangunan Cagar Budaya di Kota Bandung - Marciella, Marciella (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2019)
Heritage is one of the attractions in cultural tourism. The city of Bandung is known as a heritage city because it inherits various heritage buildings. A form in heritage conservation is through tourism. One of the stakeholders who use the heritage building for tourism is community. The example of the stakeholder is Historical Trips. Nowadays, heritage tourism is increasingly in demand, both by domestic tourists and international tourists. However, tourists’ knowledge of cultural heritage buildings after attending heritage tours held by community is unknown. The purposes of this study are to find out the characteristics of Historical Tripsâ€™ users, find out the typology of tourists who took Explore Logeweg Tour and analyze tourist knowledge of cultural heritage buildings in the central area of â€‹â€‹Bandung. Based on the result and discussion of the research, the conclusions of this study are the characteristics of Historical Tripsâ€™ users who joined Explore Logeweg are female, aged 31-50 years, work as private employees with undergraduate education, unmarried and from Bandung city. The typologies of cultural tourists who take part in the Explore Logeweg Tour held by the Historical Trips are the purposeful cultural tourist, the sightseeing cultural tourist, the serendipitous cultural tourist, and the casual cultural tourist. Tourists who attended Explore Logeweg Tour have enough and good knowledge of cultural heritage buildings in the central area of â€‹â€‹Bandung. The level of their knowledge is at the level of knowing and understanding (comprehension).